RESPONSE OF KENAF (Hibiscus cannabinus Linn.) TO FERTILIZERS AND ARBUSCULAR MYCORRHIZA IN A NUTRIENT DEGRADED ALFISOL IN IBADAN, SOUTHWESTERN NIGERIA (2011)
High and sustainable kenaf production in a fragile tropical soil requires the use of soil amendments. Arbuscular Mycorrhizae (AM) are important for nutrition of plants in nutrient depleted soils of the tropics. Due to insufficient information on kenaf production using fertilizers and AM, the effects of fertilizers and AM on soil chemical properties, growth and fibre yield of kenaf were investigated. Screenhouse and field experiments were conducted at the Institute of Agricultural Research and Training, Ibadan. The AM colonization of kenaf was assessed in the screenhouse experiment consisting of 2 x 12 x 2 factorial in a Randomized Complete Block Design (RCBD) with three replicates. The treatments were with mycorrhiza (M+) and without (M-), twelve levels of fertilizers: 0, NPK 20:10:10 (60 kgN/ha), organic (20, 40, 60, 80 and 100 kgN/ha), and organo-mineral (20, 40, 60, 80 and 100 kgN/ha) and two kenaf varieties (Cuba 108 and Tiannug 1). The higher yielding variety (Cuba 108) was used on the field to determine the optimum fertilizer rate for fibre production. The experimental design was split-plot in RCBD. Mycorrhizal inoculation was the main plot and twelve fertilizer levels as the sub-plot with three replicates. Residual effect of the treatments was also determined. Data on soil chemical properties, AM Root Colonization (RC), growth and yield parameters were collected and analysed using descriptive statistics and ANOVA. Screenhouse and field experimental soils were low in organic matter with 15.0 g/kg and 13.0 g/kg, respectively. Under screenhouse, AM colonization ranged from 14.4 to 78.1 % in the two varieties of kenaf. Inoculated Cuba 108 at 40 kgN/ha Organo-Mineral Fertilizer (OMF) had significantly (p<0.05) higher stem girth (1.8 cm), plant height (275.2 cm), RC (79.8 %), bast (9.6 g/pot) and core (19.9 g/pot) yields than other treatments. On the field, optimum bast and core yields of 3.8 and 9.4 t/ha respectively were obtained at M+ 40 kgN/ha OMF. Comparing 60 kgN/ha of fertilizers, M + OMF had significantly (p<0.05) highest bast and core yields followed by M+ NPK and M- OMF while M- Organic Fertilizer (OF) had the least. After harvesting, M- 100 kgN/ha OF had the highest organic matter, 25.9 g/kg; total N, 0.8 g/kg; available P, 6.8 mg/kg; exchangeable K, 0.4 cmol/kg and Ca, 9.6 cmol/kg. For the residual effect, M+ 100 kgN/ha OF had significantly (p<0.05) highest RC (69.0%), bast (2.7 t/ha) and core (5.8 t/ha) yields. Considering the 60 kgN/ha of fertilizers, organic had the highest bast and core yields followed by organo-mineral and inorganic. The highest organic matter was observed in M- 100 kgN/ha OF. Cuba 108 and Tiannug 1 roots were highly colonized by arbuscular mycorrhiza, while the optimum bast and core yields were observed in the inoculated Cuba 108 at 40 kgN/ha of organo-mineral fertilizer. Management of organo-mineral fertilizer along with indigenous mycorrhizae will reduce the application of chemical fertilizers and ensure optimum quantitative yield of kenaf under the assayed soil conditions